Database for a high performance and stability demanding command and control system - Johansson, Sofia (My University, 2010)
The purpose of this Master Thesis was to evaluate the possibility to use a database for data storage in a Command and Control system being built by SAAB AB (Saab) for Estonia. Today the data storage consists of a distributed data model and this complicates the wanted functionality. Data to be stored in the database was analysed and modelled into EERdiagrams. The diagrams were then transformed into database schemas that had to be tested. The database had to be changed during the thesis to get faster. The evaluation tests were performed by using a Java program that created data of the correct format and the data was then used to test the database performance. The results from this thesis were found to fulfil the system demands when using the test data and test program written. The results will need further evaluation before it is possible to fully understand how including this database would affect the system. Syftet med den här rapporten var att testa möjligheten att använda en databas i ett ledningssystem som byggs av Saab för Estland. Idag består datalagringen av en distribuerad datamodell som komplicerar åtkomsten av de naturliga relationerna som finns mellan data i systemet. Den data som skulle utgöra databasen analyserades och modellerades till EER-diagram. Diagrammen översattes till ett databasschema som låg till grund för databasen. Databasen testades och ändrades för att bli snabbare. Ett Javaprogram skrevs för att skapa data på rätt format, denna data användes sen för att testa databasen. Även testen utfördes genom ett egenhändigt skrivet testprogram i Java. Resultaten uppnådda under detta projektarbete ansågs vara tillräckliga för att uppfylla kraven när testdata och testprogram användes. För att fullt ut kunna veta hur systemet skulle påverkas av att ersätta dagens datalagringsmodell med en databas måste fler test göras där tillgång till den verkliga datan och systemet finns.
Keywords: Programvaruteknik; Software Engineering